2015
DOI: 10.13187/ejm.2015.8.88
|View full text |Cite
|
Sign up to set email alerts
|

Research Influence Biological Active Agents in the Course of Regulation of Functional Activity of Platelets and System of a Haemostasis

Abstract: It is shown that the flavonoid pulikarin suppresses activity of an adenylate cyclase and reduces level intracellular [Ca 2+ ], perhaps its effect is connected with inhibition of a gain of cytoplasmatic Ca 2+ as at the expense of its entrance outside, and release from intracellular storages. Perhaps, oppression of fluorescence of membrane-bound Ca 2+ is connected with inhibition of a pulikarin of release of calcium from intracellular depots. The inhibiting effect of a pulikarin on ADP-induced aggregation of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Тo evaluate the effectiveness of the anticoagulants in practice, clinics have used the rate of double the plasma clotting time or human blood counts in some coagulant tests compared with the readings before drug administration (Ng et al, 2003). In vitro, we showed that the effective concentrations of the studied compounds (APTT, PT, TT, ReaClot) decreased with an increase in the degree of sulphation; similar findings for sulphates of polysaccharides from various types of vegetation have been found in multiple works (Almedia-Lima et al, 2010;Nasirov et al, 2020;Cipriani et al, 2009;Nadjimova et al, 2020;Khoshimov et al, 2015;Luo et al, 2013;Maas et al, 2012;Silva et al, 2012).…”
Section: Resultssupporting
confidence: 82%
“…Тo evaluate the effectiveness of the anticoagulants in practice, clinics have used the rate of double the plasma clotting time or human blood counts in some coagulant tests compared with the readings before drug administration (Ng et al, 2003). In vitro, we showed that the effective concentrations of the studied compounds (APTT, PT, TT, ReaClot) decreased with an increase in the degree of sulphation; similar findings for sulphates of polysaccharides from various types of vegetation have been found in multiple works (Almedia-Lima et al, 2010;Nasirov et al, 2020;Cipriani et al, 2009;Nadjimova et al, 2020;Khoshimov et al, 2015;Luo et al, 2013;Maas et al, 2012;Silva et al, 2012).…”
Section: Resultssupporting
confidence: 82%